Accuracy of Dynamic Computer-Aided Implant Surgery for Biconometric Implant Positioning: A Retrospective Case Series Analysis - Luca Comuzzi; Tea Romasco; Massimo Del Fabbro; Margherita Tumedei; Luca Signorini; Francesco Inchingolo; Lorenzo Montesani; Giulia Marchioli; Carlos Fernando Mourão; Adriano Piattelli; Natalia Di Pietro (Osteology)
Background/Objectives: This retrospective study assessed the accuracy of implant positioning with dynamic computer-aided implant surgery (dCAIS) for Toronto Bridge fabrication, using a conometric prosthetic concept and a new intraoral splinting technique (CLIKSS). It compared discrepancies across various anatomical regions, bone qualities, and implant sites. Methods: This study involved 52 patients undergoing full-arch rehabilitation (17 in the mandible, 30 in the maxilla, and 5 in both), with 366 implants placed (125 in the mandible, 241 in the maxilla; 128 in post-extraction sites, and the remainder in healed sites). All implants were immediately loaded. Precision was assessed by measuring linear and three-dimensional (3D) angular deviations between planned and actual implant positions. Results: Measurement errors for apical linear and 3D deviations at the apex and entry point ranged from 0.24 ± 0.10 to 0.55 ± 0.57 mm, and angular deviations varied from 0.32 ± 0.65° to 0.35 ± 0.71°. Maxillary measurements were significantly higher at the entry, apical, and vertical levels, even when comparing anterior and posterior regions with the corresponding mandibular areas, while no differences were found in the angular deviation. Significant discrepancies were observed among different mandibular bone types. Maxillary post-extraction sites exhibited significantly greater deviations than mandibular sites in all parameters except angular deviation. No significant differences were found between healed and post-extraction sites within the same jaw. Conclusions: dCAIS improved implant placement accuracy, leading to predictable prosthetic outcomes, especially during parallel multi-implant insertions. This report introduced dCAIS for conometric/biconometric implant placement combined with the innovative CLIKSS technique as an effective intraoral split method for this prosthesis connection.